Performance analysis and optimization of an irreversible dual-cycle based on an ecological coefficient of performance criterion - Ust, Y; Sahin, B; Sogut, OS (ELSEVIER SCI LTD, 2005)
An ecological performance analysis for an irreversible dual cycle has been performed by employing the new thermo-ecological criterion as the objective function. The objective function is the ecological coefficient of performance (ECOP) and defined as the power output per unit loss rate of availability. A comprehensive numerical study is carried out to investigate the general and optimal performances of the irreversible dual-cycle having a finite-rate of heat transfer, heat leak and internal irreversibilities based on the ECOP objective function. Comparisons with an alternative ecological function defined in the literature and also with the maximum power output condition are provided to establish the utility of the new ecological performance coefficient. The results indicate that the dual cycle considered working at maximum ECOP conditions has a significant advantage in terms of entropy-generation rate and thermal efficiency. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: ecological optimization; irreversible dual-cycle; performance analysis; ENTROPY GENERATION MINIMIZATION; TIME HEAT ENGINES; THERMODYNAMIC SYSTEMS; OPTIMAL PATHS; OTTO CYCLE; MODEL; Energy & Fuels; Engineering